Ethno-Religiosity in Orthodox Christianity: A Source of Solidarity & Multiculturalism in American Society - Durante, Chris (Religions, 2015)
This study will analyze the processes of community organization implemented by Eastern Orthodox Christian ethno-religious groups, and Greek Orthodox Christian communities in particular, to establish themselves in American civil society. It will be argued that the symbiotic relationship formed between ethnicity and religion in this tradition, as well as the democratized grassroots mode of community organization that American civil society fosters, contributes to a strong sense of belonging amongst members of the ethno-religious Orthodox Christian congregations. In turn, this sense of belonging has produced a multi-layered mechanism for solidarity-building in these communities. It will then be suggested that in addition to contributing to America's religious diversity, the preservation of ethno-linguistic heritage by the various Orthodox Christian churches simultaneously contributes to America's poly-ethnicity and linguistic diversity as well. Last, it will be argued that the continued survival of ethno-religiosity in American Orthodoxy can either lead to further isolation amongst the separate ethnic congregations, or it can alternatively open avenues for the cultivation of a form of Orthodox Christian multiculturalism that supports neither homogeneity nor isolationism.